Torre: gamearte por uma descensão ao real - Pires, João Pedro Teles (2024)
In this paper we propose the exploration of the process of creating the game art object entitled Turret. To do this, it is first necessary to establish the language used through the research. I find in essay writing (Adorno, 2003; Larrosa, 2003) a way of giving way to poetic and creative thinking that unites the process of creation and research work, a way of understanding these works as a single effort, and questioning, from the field of Art, some precepts and values ​​of the academic production of knowledge. In sequence, we seek to update the concept of game with some of the prominent authors such as Huizinga (2000), Caillois (2017) and McGonigal (2011) in order to find the meanings of game as a significant cultural artifact for the human experience. In this discussion, we pay attention to the notion that games and players are violent or disseminators of uncritical violence, questioning it from the perspective of Visual Culture and the hypervisualization of images (Martins, 2006;2010). From this perspective, we think about the occurrence of violence in and around games and digital communities, and how this manifests and acts in both directions between the digital world and the real world (De Abreu, 2014a; 2014b). Through language, memes are established as ideological disseminators (Chagas, 2018) that help in the emergence of digital communities of the most diverse natures. We then turn to the act of playing, and how this becomes indicative of different human-machine interactions that focus on the cognitive and interpretative capabilities of games beyond uncritical entertainment (Majkowski, 2017), affirming that there are several paths between the minds of the creator and the player (Leino, 2012) and that these relationships can be anticipated, established or ignored between them, which makes games a powerful storytelling tool (Murray, 2003). Finally, the creative process is scrutinized  (Salles, 2004) and thought on how it appropriates concepts from self-writing (Smith and Watson, 2002; Faedrich, 2015) and game art (Venturelli, 2006, 2019), to contemplate the path between the artist’s notebooks (Cirillo, 2011) to the digital medium, and how this gesture of creating art communicates with emotions (Sartre, 2006), more specifically with pain, ecstasy and the transcendence of human experience (Bataille, 1988), referring to the literature that addresses self-injurious behaviors (Araújo, 2019) and how these behaviors refer to social networks and digital environments (Silva, Souza and Faria, 2019).